On the use of satellite remote sensing in archeology - Agapiou, Athos; Alexakis, Dimitrios D.; Sarris, Apostolos; Hadjimitsis, Diofantos G. (My University, 2019)
Remote sensing has been successfully used in the past for the exposure of shallow buried antiquities. The detection of these remains is mainly based on the photo interpretation of high-resolution satellite or aerial imagery. This procedure is focused on the identification of crop marks using visible and near infrared (VNIR) spectrum response (e.g. vegetation indices), which is sensitive to vegetation stress. Although several studies are usually performed based on adequate spatial resolution datasets, the use of freely available satellite data or ground spectral signatures for the detection of crop marks is quite limited. This study presents three different approaches and case studies on the use of such remote sensing in archaeological applications. The first part introduces the so-call 'Archaeological Index', an index sensitive to crop marks developed for detecting archaeological antiquities based on the optimal spectral bands of satellite images. This is followed by an image-based method intended for the detection of crop marks using satellite data of inadequate spatial resolution (medium spatial resolution). Finally, the potential applications of the forthcoming European Space Agency's (ESA) satellite sensor, Sentinel-2, for archaeological studies is examined. The results outlined here reveal the potential use of satellite remote sensing and ground spectroscopy for the identification of buried archaeological remains through crop marks.
Keywords: Archaeology; Crop marks; Cyprus; Satellite remote sensing; Spectroscopy; Thessaly